Temporal and energetic scale of solid matter interaction phenomena occurring during femtosecond ablation of solids - Vadillo-Pérez, José Miguel; Carrasco-García, Irene María; López-Claros, Marina; Laserna-Vázquez, José Javier (My University, 2013)
Ablation using femtosecond lasers exhibits significant differences with that at the nanosecond timescale, where the concurrence of photochemical and photothermal processes taking place during the photon absorption govern the process. In the ultrashort regime, the several phenomena involved in the laser-matter interaction are markedly different. Thus, a prior comprehension of the processes is required in order to extend the range of current applications and improve the analytical results. Our current studies are facing fundamental and applied studies with the aim of better understanding laser-matter interaction processes in condensed phase using femtosecond lasers. To achieve this goal, we have designed experimental strategies expecting to improve the knowledge of the timescale and onset generation of chemical species and surface alterations during femtosecond ablation of solids. Time-resolved optical emission spectroscopy, time-of-flight mass spectrometry and time-resolved phase-change microscopy are currently implemented. The combined use of the cited techniques is allowing the experimental determination of the energy threshold, temporal regime and macroscopic effects occurring in a variety of materials as a consequence of the interaction with an ultra-short laser pulse. The core of the experiment is a 80 Mhz, 100 nJ, 400 fs Ti-Saphire oscillator that is additionally subjected to chirped pulse amplification to produce an output of 3,5 mJ at 35 fs and a maximum repletion rate of 1 KHz. Different wavelengths (800, 400 and 266 nm) are achievable. An intensified CCD and a dual-state reflectron equipped with a cassegrain reflective optics are used for the analysis of the photons and ion generated after laser irradiation. Additionally, a pump-probe microscope with a temporal resolution better than 500 fs has been designed to allow time-resolved studies of phase-change in the ablated samples.
Keywords: Química analítica